Evaluation of Geriatric Patients’ Functional Condition as the Indicator for Nursing Care Required - Doroszkiewicz, Halina; Sierakowska, Matylda; Lewko, Jolanta; Ostrowska, Aneta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Background. The aim of the work was to evaluate the functional condition of elderly people hospitalized at the Geriatrics Ward and to determine the scope of their nursing needs. Material and method. Survey-based research was carried out among a group of 100 patients 60 years of age or older, consecutively admitted to the Geriatrics Ward of the MSW (Ministry of Interior) Hospital in Białystok. The study tool was standardized questionnaires for the evaluation of elderly people’s condition. Self-care was assessed on the basis of the Barthel scale, the ability to perform complex daily living activities, on the basis of questions from the I-ADL scale, the risk of bedsores, according to the Norton scale, the emotional state, on the basis of the Geriatric Depression Scale according to Yesavage’a, the cognitive functions, on the basis of the AMTS, and the fall risk, on the basis of the Tinetti test. The research was supplemented with a self-constructed survey questionnaire enquiring about socio-demographic data and self-evaluation of the respondents’ health. Statistical analysis was performed with the use of STATISTICA v. 13.0 statistical package. The p value lower than 0.05 was regarded as statistically significant difference. Results. The elderly persons participating in the study were characterized with an advanced age, poor health condition and complex disability. Three fourths of the subjects were seriously dependent on others’ help in performing complex daily living activities. More than a half (60.0%) of the studied elderly people displayed an abnormal result regarding the emotional state, and 42.0%, regarding cognitive functions. Every second person ran a high risk of falling and developing bedsores. Conclusions. Advanced age, deteriorating health and complex disability increase the need for care. Evaluation of the functional condition of elderly people with the use of standardized questionnaires is a significant indicator of the required nursing care.